Lack of relationship between epidermal denervation by capsaicin and incisional pain behaviours: A laser scanning confocal microscopy study in rats. (12th April 2020) - Uhelski, Megan L.; McAdams, Brian; Johns, Malcolm E.; Kabadi, Rajiv A.; Simone, Donald A.; Banik, Ratan K.
Abstract: Background: Spontaneous pain after surgical incision is a significant problem for most post‐operative patients. Pain management that relies on opioids is hindered by numerous side effects, fuelling interest in non‐opioid alternatives and multimodal approaches. Subcutaneous capsaicin infiltration has shown potential for reducing post‐operative pain, but there are unanswered questions about safety and possible side effects. In adult rats, we characterized the analgesic effects of pre‐operative capsaicin infiltration into the skin prior to plantar incision and assessed wound healing and epidermal innervation. Methods: The surgical site on the plantar surface of the rat hind paw was infiltrated with 1% capsaicin or vehicle 30 min or 1 week prior to surgical incision. Spontaneous and evoked pain behaviours were assessed. Digital images of incised hind paws were used to quantify the surface area of the wound after suture removal. Epidermal nerve fibre quantification was performed on peri‐incisional tissue biopsies. Results: Intraplantar administration of capsaicin 30 min before surgical incision attenuated spontaneous pain behaviours, heat hyperalgesia, epidermal innervation, but it did not alter the rate of wound healing. Incisional pain hypersensitivity returned to baseline 2 weeks post‐incision, at a time when no recovery of epidermal innervation is observed. Conclusions: Subcutaneous infiltration of capsaicin prior to surgical incision attenuated incision‐induced pain behaviours and reduced epidermal innervation around the incision site. The long‐lasting epidermal denervation by capsaicin had no impact in the rate of wound healing and recovery from pain behaviours. Significance: Pre‐operative capsaicin infiltration attenuated spontaneous pain‐like behaviour and prevented the development of heat hyperalgesia following plantar skin incision. While capsaicin caused long‐lasting and widespread loss of epidermal and dermal nerve fibres, there was no measurable impact on the rate of wound healing. Pre‐ or intra‐operative infiltration of capsaicin into surgical sites could act as a safe prophylactic for post‐operative pain and reduce the need for opioids during recovery.